Asuhan Kebidanan Kompehensif pada Ny. S di RSIA Masyita Makassar - Nur Emisah; Azrida M; Suryanti S (Window of Midwifery Journal, 2025)
Continuity of Care is a comprehensive and continuous approach to care for mothers and babies, from pregnancy, childbirth, postpartum, newborn care, and family planning services. Its primary goal is to optimally monitor the condition of the mother and baby, build a trusting relationship between the midwife and the mother, and improve the quality of midwifery care. The method used in providing midwifery care in this study is the midwifery management approach, which includes Varney's 7 steps and the SOAP method. Based on the results of research on Mrs. S's fourth pregnancy with an obstetric history without miscarriage, the pregnancy process was physiological, and no complications were found during the gestation period. During labor, Mrs. S gave birth spontaneously without experiencing complications. Mrs. S's baby was born spontaneously on February 3, 2025, at 22.20 WITA with a weight of 2,820 grams; the Apgar Score was recorded as 8/10. During Mrs. S's postpartum period, there were no danger signs at all that caused complications. Care for prospective family planning on February 7, 2025, the mother wanted to use the contraceptive implant before the postpartum period ended, namely March 4, 2025. All stages from pregnancy to family planning services took place normally without any complications. These findings are expected to be learning materials and input in improving the quality of midwifery services as a whole, from early pregnancy to family planning.